ANALISIS PENGARUH BUSINESS ADMINISTRATION COMPETITION (BAC) TERHADAP MOTIVASI BELAJAR, KECERDASAN EMOSIONAL DAN PENINGKATAN KOMPETENSI MAHASISWA YANG BERDAYA SAING GLOBAL - Fandy Bestario Harlan; Yulinda Tarigan (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
This study aims to determine the effect of Business Administration Competition on student learning motivation, emotional intelligence and increasing competence of students' global competitiveness. The variables of this research are the BAC Competition (X1), learning motivation (Y1), emotional intelligence (Y2) and increasing competence of students' global competitiveness (Y3). This study used a quantitative approach using a sample of students in Business Administration study program who had participated in BAC competitions at both Polibatam and National levels. Data processing techniques in this study used SPSS 20 software. The population in this study were all students who participated in BAC which consisted of Secretarial competition, Meeting design competition, MC competition, Business presentation competition, Web design competition, Business data processing competition and Business plan. . The sample size of 28 students was determined by purposive sampling technique. Data collection was carried out by means of questionnaires and observation. Data analysis was performed using descriptive analysis and simple linear regression. The results of this study concluded that there is an effect of the BAC Competition on each variable of learning motivation, emotional intelligence and increasing competence of students' global competitiveness.